THE ROLE OF NATURAL FORESTS IN PROMOTING ECO-TOURISM DEVELOPMENT IN NINEVEH GOVERNORATE - Shakir Mahmood AWAD; NASER NAZAR MOHAMED RAOF (Scholar Express Journals, 2023)
The role of the tourism sector and its development at the global level has a great impact on the development of national income, as well as being a relaxing factor for members of society to spend time and gain and develop experiences. Perhaps one of the most prominent types of tourism is ecotourism, which depends on the element of nature and environmental sustainability as its basis. Forests have long been associated with recreational and tourism experiences around the world, where relaxing outdoors is an important part of the daily lives of most of the world's population. Since Mosul's forests cover the largest area of the city, it is important to highlight the importance of exploiting this green space in promoting ecotourism in the city of Mosul. The research aims to highlight the importance of natural resources in the city of Mosul represented in forests to achieve ecotourism from the definition of ecotourism, its concepts, objectives, conditions of application and its economic, environmental and social impact. This leads to realistic development at the environmental, local and national levels, as well as a positive impact on sustainable development
Keywords: realistic development; positive; sustainable; impact